Development Of Recombinant Immunotherapeutics for Triple-Negative Breast Cancer (TNBC) - Ngwenya, Takunda (Institute of Infectious Disease and Molecular Medicine, 2024)
Breast cancer is the most common form of female malignancy globally. There are several subtypes of breast cancers including Triple-negative breast cancer (TNBC), which is mainly characterized by a lack of expression of the estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2). TNBC is one of the most aggressive subtypes of breast cancer, with a 20% lower disease-free and overall survival rates than is observed for non-TNBC patients. It is characterized by higher rates of aggressive relapse, high metastatic potential, shorter survival rate and an overall aggressive and invasive clinical course. This subtype is most prevalent in young (≤50 years) female patients of African ancestry compared to other ethnicities. TNBC poses a significant challenge due to the lack of molecular targets. The current treatment of TNBC is achieved by chemotherapy, surgery and radiotherapy, collectively referred to as tri-modality therapy. However, tri-modality therapy results in disease relapse and adverse side effects. As a result, an ongoing need exists to develop a range of targeted therapeutics to effectively treat the majority of TNBC tumours. These targeted anti-cancer therapies aim to enable the selective killing of cancer cells while minimizing harm to healthy cells. This selective cytotoxicity would result in a significant improvement in TNBC treatment efficacy while reducing the side effects. The development of targeted anticancer therapies for TNBC is an active area of research and scientists are currently exploring various approaches to develop targeted anticancer therapies for TNBC and other cancer types. Antibody-Drug-Conjugates (ADCs) are proteins that combine an antibody and a toxin designed to selectively target and kill cancerous cells respectively. These are promising alternatives to conventional cancer treatment. This approach takes advantage of the specific cell surface receptors (CSRs) that are often present on cancerous cells and absent in healthy tissues. Among several CSRs that have been identified to be overexpressed in TNBC, CD90, LGR5 and EpCAM were considered for this study. Due to the limited effectiveness of full mAbs penetration into tumours, smaller antibody fragments such as scFv and Fabs have shown a greater ability to penetrate tumour tissues. These smaller antibody formats can be used to develop recombinant immunotoxins (rITs) using protein toxins as cell-killing moieties to achieve targeted destruction of cancer cells. Pseudomonas exotoxin A (ETA) is a potent enzyme that disrupts the function of eukaryotic elongation factor 2, causing inhibition of protein synthesis and leading to cell death. Due to the bacterial origin of ETA, scientists have discovered that it often triggers an unwanted humoral response in patients during clinical trials. To address this challenge, researchers have introduced mutations in the ETA gene to reduce the risk of causing an immunogenic response while preserving the cytotoxicity activity. This study aimed at developing single chain fragments of variability (scFvs) derived from publicly available sequences of antibodies that target three CSRs overexpressed in TNBC, genetically fused to wild-type ETA (wt ETA) or a mutant version of ETA that was generated using advanced computer simulation by our collaborating partner, Professor Paolo Carloni from Forschungszentrum Jülich, Germany. The mutated version is described as de-immunized ETA (dETA). The recombinant immunotoxins were generated by constructing a bacterial periplasmic expression plasmid, which included ETA or dETA fused to an scFv antibody fragment targeting each of the three biomarkers (CD90, LGR5 and EpCAM). The plasmid also contained the corresponding scFv that was inserted before the transformation of the plasmid into Escherichia coli (E. coli) BL21 for bacterial protein expression under osmotic stress conditions in the presence of compatible solutes. The rITs were then purified by immobilized metal ion chromatography (IMAC) and size exclusion chromatography (SEC). Confirmation of full-length rITs was done by sodium dodecyl-sulfate polyacrylamide gel electrophoresis (SDS PAGE) and Western blot analysis. Upon successful confirmation of full-length proteins, binding and cytotoxicity studies were conducted on TNBC cell line MDA-MB-468 using the rITs. In this study, all six designed plasmids were successfully cloned, and recombinant fusion proteins were expressed using the bacterial periplasm of E. coli BL21 as evidenced by SDS PAGE and western blot. The rITs displayed a strong binding affinity for MDA-MB-468 TNBC cells. Cytotoxicity results revealed that both ETA and dETA-rITs can both target and kill MDAMB-468 TNBC cells. ETA-based rITs exhibited more robust killing activity than dETA-based rITs, except for the rITs targeting CD90, in this case exceeding wt ETA enzymatic activity. This study showed potential for clinical application of the generated rITs' for TNBC immunodiagnostic use and the ability of ETA and dETA toxins to specifically kill TNBC antigenpositive tumour cells indicating targeted therapeutic potential. This work serves as proof of concept for investigating the use of rITs in TNBC tumour detection and patient stratification to offer personalized therapeutics.